2021
DOI: 10.3389/fcvm.2021.691548
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Exosomes in Prognosis and Developments of Coronary Artery Disease

Abstract: Exosomes, with an diameter of 30~150 nm, could be released from almost all types of cells, which contain diverse effective constituent, such as RNAs, proteins, lipids, and so on. In recent years, exosomes have been verified to play an important role in mechanism, diagnosis, treatment, and prognosis of cardiovascular disease, especially coronary artery disease (CAD). Moreover, it has also been shown that exosomes derived from different cell types have various biological functions based on the cell stimulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Increasing evidence has shown that miRNAs are related to cardiac function, disease, and cardioprotection (37)(38)(39)(40). Regarding cardioprotection, the expression of several miRNAs, such as miR-1, miR-21, and miRNA-125b, have been identified to be significantly changed due to ischemic pre-or postconditioning (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that miRNAs are related to cardiac function, disease, and cardioprotection (37)(38)(39)(40). Regarding cardioprotection, the expression of several miRNAs, such as miR-1, miR-21, and miRNA-125b, have been identified to be significantly changed due to ischemic pre-or postconditioning (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…They express micro-ribonucleic acid (RNA) and seem to have anti-inflammatory, anti-oxidative, and angiogenic properties. Introduction of EVs helped mitigate damage from reperfusion ( Chen et al, 2021 ). EVs have been utilized as a therapeutic approach in immune-mediated illness, in addition to their application in intentionally induced hypoxia to organs as in transplantation or cardiac surgery.…”
Section: Indoleamine-23-dioxygenase As a Target In Anoxic States Related To Oxidative Stressmentioning
confidence: 99%
“… 9–12 However, very little research has been conducted on the identification of restenosis-related genes and the prediction of diagnostic markers in patients with restenosis using bioinformatics analysis. 13 Some studies have found that high-sensitivity C-reactive proteins can predict increased risk of restenosis in patients with coronary artery disease; 14 others have shown that preoperative inflammatory factors such as interleukin (IL)-6, IL-8, tumor necrosis factor-alpha, and IL-23 predict restenosis risk. 15 , 16 The chief pathological features of restenosis are injury to arterial endothelial cells and proliferation of new tissue, which re-shrinks the coronary artery after stenting.…”
Section: Introductionmentioning
confidence: 99%